2012
DOI: 10.1186/cc11336
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of accuracy of optic nerve ultrasound for the detection of intracranial hypertension in the setting of acutely fluctuating vs stable intracranial pressure: post-hoc analysis of data from a prospective, blinded single center study

Abstract: IntroductionOptic nerve sheath diameter (ONSD) measurement with bedside ultrasound has been shown in many studies to accurately detect high intracranial pressure (ICP). The accuracy of point-in-time ONSD measurement in the presence of ongoing fluctuation of ICP between high and normal is not known. Recent laboratory investigation suggests that reversal of optic nerve sheath distension may be impaired following bouts of intracranial hypertension. Our objective was to compare the accuracy of ONSD measurement in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 13 publications
3
55
2
3
Order By: Relevance
“…7 This was demonstrated in the retrospective study by Rajajee et al in which a delayed reversal of ONSD after ICP fluctuations was shown. 16 However, in our study, changes in ICP were reflected by immediate changes in ONSD. In all cases ONSD reverted to baseline levels simultaneous with a decrease in ICP, directly after tracheal manipulation was stopped.…”
Section: Discussioncontrasting
confidence: 39%
See 3 more Smart Citations
“…7 This was demonstrated in the retrospective study by Rajajee et al in which a delayed reversal of ONSD after ICP fluctuations was shown. 16 However, in our study, changes in ICP were reflected by immediate changes in ONSD. In all cases ONSD reverted to baseline levels simultaneous with a decrease in ICP, directly after tracheal manipulation was stopped.…”
Section: Discussioncontrasting
confidence: 39%
“…Bilateral ocular trauma can make it impossible to perform ONSD measurement, but this is uncommon in head trauma patients. 16 In ICU settings, invasive, continuous ICP measurement with the ICP probe remains superior to this noninvasive, intermittent ONSD ultrasonography because it delivers continuous values and requires no additional skills from the attending ICU nurse. However, in emergency care and prehospital conditions ONSD measurement may be useful to distinguish between normal or elevated ICP in comatose patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the literature there are very little data on ONSD changes in patients with increased ICP secondary to ICH beyond the hyperacute or acute stage [6]. We performed serial US studies to measure ONSD in four patients with extensive hypertensive ICH followed longitudinally beyond the hyperacute and acute stage.…”
Section: Introductionmentioning
confidence: 99%